Circulating levels of CXCL11 and CXCL12 are biomarkers of cirrhosis in patients with chronic hepatitis C infection. (May 2019) - Chalin, Arnaud; Lefevre, Benjamin; Devisme, Christelle; Barget, Nathalie; Amiot, Laurence; Samson, Michel
Highlights: Circulating CXCL10, CXCL11 and CXCL12 are found in chronically infected HCV patients. CXCL11 and CXCL12 were highly upregulated in cirrhotic patients. CXCL10 and CXCL11 were higher in patients with advanced stage of inflammation. The AUROCs were 0.8147 and 0.8574 for CXCL11 and CXCL12 for the diagnosis of cirrhosis. Abstract: Background & aims: The chemokines CXCL10 (interferon ϒ-inducible protein 10 [IP-10]), CXCL11 (Human interferon inducible T cell alpha chemokine [I-TAC]), and CXCL12 (stromal cell derived factor 1 [SDF-1]) contribute to cell recruitment, migration, activation, and homing in liver diseases and their serum levels have been shown to be associated with the degree of liver inflammation or fibrosis in various etiologies. However, the data may be contradictory or insufficient, particularly for CXCL12, in the field of chronic HCV infection. Here, we aimed to provide evidence for these chemokines as biomarkers for chronic HCV infection. Methods: We analyzed the serum concentration of the three chemokines in healthy donors (n = 39) and patients (n = 87) with chronic HCV infection. Chemokine serum levels were compared to the stage of liver inflammation and fibrosis obtained from liver biopsies. Results: Serum CXCL10 and CXCL11 levels were higher at advanced stages of liver inflammation than at earlier stages, but the results were only of medium significance. Both serum CXCL11 and CXCL12 levels were significantly higher in cirrhotic patients than those with low or medium stages of fibrosis. The AUROCs were 0.8167 and 0.8574, respectively, for the diagnosis of cirrhotic patients. Conclusion: These data provide evidence for the value of CXCL10, CXCL11, and CXCL12 as biomarkers of liver inflammation and fibrosis during chronic HCV infection. Serum CXCL10 and CXCL11 levels were associated with liver inflammation, but the level of significance was insufficient. However, serum CXCL11 and CXCL12 levels were elevated in cirrhotic patients, showing equivalent diagnostic accuracy as the existing established single serum fibrosis markers or algorithms.